Features of Arabian character in Hebrew short story A chosen collection of stories (Moshe Smelaneski) paradigm (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
even though some glimmers of  peace treaties flash in  Arab – Israeli conflict horizon, the event  indicators  for  this  conflict  refer to possibility of its recurrence and outbreak  of  war at any moment. Consequently the scientific knowledge with Israeli situation Israeli human and his look at the Arabian human become a demand and a responsibility of Arab educated  people and researches who are interested in study this situation and that human . Building on  this, our research has been conducted to reveal and  know how Hebrew short story writers describe and depict the factures of Arab character. We always find them shedding light on the  character of the Arab person as an uncivilized ,illiterate, dirty' nomad, and peasant  person who is stacked to every bad features. All that bad description with  the aim of vilification of this character on  one hand  and demonstration of the superiority character person on the  other hand. مهما برقت في سماء الصراع العربي الإسرائيلي بعضُ بوارقِ معاهداتِ السلام، فإنَّ مؤشراتِ الأحداث بالنسبة لهذا الصراع تشيرُ إلى احتمالاتِ تجدُّدهِ، ونشوبِ الحرب في أيَّةِ لحظة. ومن هنا فإنَّ المعرفة العلمية بالواقع الإسرائيلي، وبالإنسان الإسرائيلي، ونظرته إلى الإنسان العربي تصبحُ مطلباً، ومسؤوليةً تقع على عاتق المثقفين والباحثين العرب، الذين يهتمون بدراسة هذا الواقع، وذلك الإنسان. انطلاقاً  من ذلك جاء بحثنا هذا من أجل معرفةِ كيفيةِ تصوير كُتَّابِ القصةِ العبريةِ القصيرة لملامح الشخصية العربية، إذ نجدهم ـــ دائماً ـــ يسلطون الضوء على شخصية البدوي أو القروي، الجاهل، القذر، المتخلِّف، الذي تلتصق به كلُّ صفةٍ سيِّئةٍ؛ وذلك  بهدف تحقير هذه الشخصية  من ناحية، وإظهار تفوق الشخصية اليهودية من ناحية أخرى.